Pengaruh Transparansi Anggaran Desa terhadap Tingkat Kepercayaan Masyarakat: Studi Survei di Desa Labuhan Haji, Kabupaten Lombok Timur - Zulkarnain, Lalu Ahmad; Galih Ahmad, Lalu (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine the effect of village budget transparency on the level of public trust in Labuhan Haji Village, East Lombok Regency. Budget transparency is considered a key instrument in strengthening village governance and enhancing public legitimacy. The study employs a quantitative approach with an explanatory survey design. Data were collected through structured questionnaires distributed to randomly selected village residents. Data analysis was conducted using descriptive statistics and simple linear regression after meeting classical assumption tests. The results indicate that village budget transparency has a positive and significant effect on public trust. Greater openness in budget planning, implementation, and reporting is associated with higher levels of trust in the village government. These findings confirm that budget transparency plays a crucial role in reducing information asymmetry and strengthening the relationship between the village government and the community. The study recommends reinforcing transparent budget practices accompanied by public participation mechanisms to sustain public trust.